In situ X-Ray Diffraction of Shock-Compressed Fused Silica - Tracy, Sally June; Turneaure, Stefan J; Duffy, Thomas S (Physical review letters, 2018)
Because of its widespread applications in materials science and geophysics, SiO_{2} has been extensively examined under shock compression. Both quartz and fused silica transform through a so-called "mixed-phase region" to a dense, low compressibility high-pressure phase. For decades, the nature of this phase has been a subject of debate. Proposed structures include crystalline stishovite, another high-pressure crystalline phase, or a dense amorphous phase. Here we use plate-impact experiments and pulsed synchrotron x-ray diffraction to examine the structure of fused silica shock compressed to 63 GPa. In contrast to recent laser-driven compression experiments, we find that fused silica adopts a dense amorphous structure at 34 GPa and below. When compressed above 34 GPa, fused silica transforms to untextured polycrystalline stishovite. Our results can explain previously ambiguous features of the shock-compression behavior of fused silica and are consistent with recent molecular dynamics simulations. Stishovite grain sizes are estimated to be ∼5-30  nm for compression over a few hundred nanosecond time scale.